Answer:
1/6
Step-by-step explanation:
So we are subtracting a negative which is the same as adding. Our equation becomes -1/3+1/2. To add fractions we need a common denominator (the denominator of a fraction is the number on the bottom) To fine the least common denominator we need to find the lowest number that both 3 and 2 go into which is 6. Then we will multiply each fraction by the number that will give us 6 for a denominator which is 2 for -1/3 and 3 for 1/2. So -1/3 times 2 is -2/6 and 1/2 times 3 is 3/6. Our equation is now -2/6+3/6. Now we will add the numerators ( the numerator is the number on the top of the fraction) and the denominators stay the same when adding or subtraction fractions -2/6+3/6=1/6
I hope this helps and please let me know if there is anything you are confused about or is still unclear, I will be happy to help!
Answer:
11 pieces.Step-by-step explanation:We must divide 8 1/4 by 3/48 1/4 = 33/4Dividing:33/4 / 3/4= 33/4 * 4/3= 33/3= 11.
Step-by-step explanation:
11 pieces.Step-by-step explanation:We must divide 8 1/4 by 3/48 1/4 = 33/4Dividing:33/4 / 3/4= 33/4 * 4/3= 33/3= 11.
Answer:
(- 4, - 12 ) , (4, 12 )
Step-by-step explanation:
Given the 2 equations
y = 3x → (1)
y = x² + 3x - 16 → (2)
Substitute y = x² + 3x - 16 into (1)
x² + 3x - 16 = 3x ( subtract 3x from both sides )
x² - 16 = 0 ( add 16 to both sides )
x² = 16 ( take the square root of both sides )
x = ±
= ± 4
Substitute these values into (1) for corresponding values of y
x = - 4 : y = 3 × - 4 = - 12 ⇒ (- 4, - 12 )
x = 4 : y = 3 × 4 = 12 ⇒ (4, 12 )
Answer: I can only see the big boxes so will answer them
5/6 - 1/3
Multiply the two denominators together get 18
Then multiply the bottom denominator with the opposite numerator
The sum has now changed to:
15/18 - 6/18
15 - 6 = 9
9/18 can then be simplified to 1/2